Public Perspective toward Car-free Day Program as a Public Open Space: A Case Study in Klaten, Central Java : Public open space in small town - Muhammad Aziz Proklamalatu; Nurul Hidayati (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2021)
Public open spaces are the core component of sustainable urban development which can provide multiple advantages. There has been growing interest from policy-makers to implement car-free day (CFD) either in big cities or small cities to promote economic activity, public mental health, and wellbeing. Here, we conducted an exploratory study to describe the characteristic of CFD as an open space allocation and its characteristic as well as explores the perspective of urban residences regarding the utilization of road space as open space viewed from physical, social, and economical functions. Results indicate that circulation lines, public facilities as well as street furniture are well organized although there is a small issue regarding pedestrian space that was minimum. Respondents believe that public open spaces should consider prioritizing the comfort and active engagement support while they do not aware of the discovery aspect. The vast majority of respondents (32%) purposes are to have an exercise at CFD.